Environmentally friendly microporous sound-absorbing ceramic prepared using river and lake bottom mud and preparation method thereof

By covering non-woven fabrics in the ceramic slurry injection molding process, the problem of insufficient formulation and preparation methods when preparing porous sound-absorbing ceramic materials as raw materials is solved, the improvement of material performance and the feasibility of large-scale production are achieved, and the goals of environmental protection and resource utilization are achieved.

CN118206357BActive Publication Date: 2025-03-18JIANGSU ENVIRONMENTAL PROTECTION GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410141657.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-01
Publication Date
2025-03-18
Estimated Expiration
2044-02-01

AI Technical Summary

Technical Problem

In the prior art, when preparing porous sound-absorbing ceramic materials using river and lake bottom mud as raw materials, they face shortcomings in the formula and preparation methods of ceramic slurry, resulting in the inability to effectively improve the compressive strength and noise reduction and sound absorption performance of the material, and the preparation efficiency is low and the yield is low, so it cannot be suitable for large-scale production.

Method used

The injection molding process is adopted to inject the ceramic slurry into the mold and cover the non-woven fabric, stand in a mold, and then dry and sintered after removing the non-woven fabric to prepare environmentally friendly microporous sound-absorbing ceramics. This method improves the acoustic and mechanical properties of the material by controlling the formulation and stirring process of the ceramic slurry.

Benefits of technology

It effectively avoids cracking of ceramic blanks, improves the yield and production efficiency of materials, and is suitable for large-scale production of porous sound-absorbing ceramics. At the same time, by efficient resource utilization of river and lake bottom mud, environmentally friendly treatment of solid waste is achieved and production costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118206357B_ABST
    Figure CN118206357B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of river and lake sludge treatment, and provides an environmentally friendly microporous sound-absorbing ceramic prepared by using river and lake bottom mud and a preparation method thereof. The process includes mixing river and lake bottom mud, fly ash, diatomaceous earth, expansion agent, dispersant, and gelling agent, adding water to form an initial slurry; ball milling the initial slurry to obtain a premixed liquid; adding a foaming agent to the premixed liquid, stirring once, then adding a foam stabilizer, stirring twice, to obtain a ceramic slurry; injecting the ceramic slurry into a mold, covering the surface of the ceramic slurry in the mold with a non-woven fabric, and standing to form a mold; then removing the non-woven fabric, demolding to obtain a green body; drying and sintering the green body to obtain an environmentally friendly microporous sound-absorbing ceramic. The present invention can avoid the occurrence of green body cracking through process improvements in injection molding and other links, greatly improve the yield rate of material preparation, and improve the production efficiency of sound-absorbing ceramics, and is suitable for the preparation of large-scale porous sound-absorbing ceramics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of river and lake bottom mud treatment, and specifically relates to an environmentally friendly microporous sound-absorbing ceramic prepared by utilizing river and lake bottom mud and a preparation method thereof. Background Art

[0002] As a reservoir of external pollutants, river and lake sediments are the main internal source of pollution; taking Taihu Lake as an example, the treatment of polluted sediments is an important part of the comprehensive management of Taihu Lake's water environment. River and lake sediments contain a large number of microorganisms and excessive metals. Long-term disorderly stacking will cause harmful pollution. In river and lake dredging projects, the treatment and disposal of river and lake sediments has become a difficult problem in solid waste disposal. River and lake sediments contain relatively rich clay mineral components such as silicon oxides, which can be used as the basic raw material components of sound-absorbing ceramic materials. Using river and lake sediments as the basic raw material to prepare porous sound-absorbing ceramic materials is one of the effective ways to realize the resource utilization of river and lake sediment treatment and disposal, and it can also reduce the raw material cost of sound-absorbing materials.

[0003] However, using river and lake sediment as a basic raw material with a large proportion (>55%) to prepare porous sound-absorbing ceramic materials requires overcoming many difficulties - the ceramic slurry formula needs to be developed, and the preparation method also needs to be improved. Especially for porous sound-absorbing ceramic materials, it is necessary to improve the material performance from all aspects of the formula and preparation method to achieve a comprehensive improvement in the mechanical properties such as compressive strength of the material and the acoustic properties such as noise reduction and sound absorption.

[0004] In the prior art, gel injection molding is a feasible method for preparing ceramic materials. This process forms a macromolecular network structure through chemical reactions inside the ceramic slurry, thereby solidifying the ceramic powder in situ into a ceramic body. As for porous ceramic sound-absorbing materials, in terms of raw material formulation, it is necessary to select suitable chemical agents that can play a role in gelling, foaming, etc., based on the basic raw materials of river and lake sediments, which account for a large proportion, and the functional requirements of pore-forming sound absorption, and consider their dosage ratios to form a good ceramic slurry and ensure the acoustic properties of the material after solidification; in terms of preparation methods, the ceramic slurry is slowly solidified after injection molding, but during the drying process of the wet blank, cracks easily appear on the surface, resulting in low preparation efficiency and low yield of porous ceramic sound-absorbing materials, which cannot be applied to the treatment and disposal of large-volume river and lake sediments or the industrial-scale production of sound-absorbing materials. Summary of the invention

[0005] The present invention provides an environmentally friendly microporous sound-absorbing ceramic prepared by using river and lake bottom mud and a preparation method thereof, so as to solve the deficiencies in raw material formula and preparation method of the production process of preparing porous sound-absorbing ceramic using river and lake bottom mud as one of the raw materials in the prior art.

[0006] The first aspect of the present invention provides a method for preparing environmentally friendly microporous sound-absorbing ceramics, comprising injection molding a ceramic slurry, injecting the ceramic slurry into a mold, covering the surface of the ceramic slurry in the mold with a non-woven fabric, and allowing the mold to stand; then removing the non-woven fabric and demolding to obtain a green body; drying and sintering the green body to obtain an environmentally friendly microporous sound-absorbing ceramic.

[0007] Optionally, the non-woven fabric is a polyester fiber water-permeable non-woven fabric.

[0008] Optionally, the non-woven fabric has a thickness of 0.3 mm.

[0009] Optionally, the mold is polygonal, with at least one side having a length ≥ 20 cm.

[0010] Optionally, the mold is circular, and the circular diameter is ≥20 cm.

[0011] Optionally, the standing time for the standing mold is 16 to 28 hours.

[0012] Optionally, the drying temperature is 40-55° C., and the moisture content of the green body after drying is ≤3%.

[0013] Optionally, the sintering comprises: placing the dried green body in a sintering furnace, increasing the sintering temperature to 1200-1350° C. at a rate of 5° C. / min, and keeping the temperature for 2 hours.

[0014] Optionally, the preparation method of the ceramic slurry includes: mixing river and lake sediment, fly ash, diatomaceous earth, an expander, a dispersant, and a gelling agent, and adding water to form an initial slurry; the solid content of the initial slurry is 38 to 50 vol%; ball milling the initial slurry to obtain a premixed liquid; adding a foaming agent to the premixed liquid, stirring once, and then adding a foam stabilizer, stirring a second time to obtain a ceramic slurry.

[0015] Optionally, the stirring speed is 600-800 rpm, and the stirring time is 2-4 minutes.

[0016] Optionally, the initial slurry is ball-milled at a rotation speed of 200 to 500 rpm, and the ball-milling time is 2 to 5 hours.

[0017] Optionally, the secondary stirring has a rotation speed of 800 to 1000 rpm and a stirring time of 1 to 2 minutes.

[0018] The second aspect of the present invention provides an environmentally friendly microporous sound-absorbing ceramic obtained by the above preparation method.

[0019] Optionally, the environmentally friendly microporous sound-absorbing ceramics, measured by dry weight, have a base material comprising 55-80 parts of river and lake sediment, 20-40 parts of fly ash, and 3-8 parts of diatomaceous earth; the agents added to the base material, measured by mass fraction of the base material, include 2-5% of an expansion agent, 1-2% of a dispersant, 1-2% of a gelling agent, 0.8-2% of a foaming agent, and 1-3% of a foam stabilizer.

[0020] Optionally, the swelling agent is sodium bicarbonate.

[0021] Optionally, the foaming agent is sodium laurylamphoacetate.

[0022] Optionally, the foam stabilizer is gluconolactone.

[0023] Optionally, the dispersant is any one or more of PMAA-NH4, water glass or sodium citrate.

[0024] Optionally, the dispersant is a combination of PMAA-NH4, water glass and sodium citrate, and the combined mass ratio is 2:1:1.

[0025] Optionally, the gelling agent is any one or more combinations of plant glue, epoxy resin or sodium alginate.

[0026] Optionally, the gelling agent is a combination of vegetable glue, epoxy resin and sodium alginate, and the combined mass ratio is 2:2:1.

[0027] A third aspect of the present invention provides a sound barrier, which comprises the above-mentioned environmentally friendly microporous sound-absorbing ceramic or the environmentally friendly microporous sound-absorbing ceramic prepared by the above-mentioned preparation method.

[0028] The preparation method of the environmentally friendly microporous sound-absorbing ceramic of the present invention can avoid the occurrence of cracking of the blank by covering the non-woven fabric in the injection molding process, greatly improve the yield rate of material preparation, improve the production efficiency of sound-absorbing ceramics, and is suitable for the preparation of large-scale porous sound-absorbing ceramics. Furthermore, the environmentally friendly microporous sound-absorbing ceramic of the present invention, whose main raw materials are river and lake sediments, fly ash and other solid wastes, realizes efficient resource utilization, eliminates river and lake sediments, one of the solid waste pollution, solves the problem of lake sediment disposal, and saves land; it can batch process and dispose of river and lake sediment solid waste, promote its resource utilization efficiency, improve the added value of solid waste, and use it to control noise pollution, achieving the effect of treating pollution with pollution; and in the preparation method of the present invention, in the foaming and stabilizing foaming process, the processes such as controlling the addition of agents and stirring are effectively improved to effectively improve the sound absorption performance of porous ceramic materials; the preparation process is simple, highly repeatable, and easy to achieve large-scale mass production. In addition, the preparation process of ceramic materials does not involve expensive equipment such as molding machines and cold isostatic presses, which reduces production costs; water is used as a solvent instead of traditional organic solvents, no organic matter is volatilized during the sintering process, and carbon emissions are reduced. It is environmentally friendly and no toxic substances are discharged. It is an environmentally friendly microporous sound-absorbing ceramic product. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The present invention is a flow chart of a preparation method according to an embodiment of the present invention.

[0030] Figure 2 This is a CT characterization image of the sound-absorbing ceramic material of the present invention.

[0031] Figure 3 This is a SEM electron microscope image of the sound-absorbing ceramic material of the present invention.

[0032] Figure 4 This is another SEM electron microscope image of the sound absorbing ceramic material of the present invention.

[0033] Figure 5 Graph showing the sound absorption coefficient of the sound absorbing ceramic material according to an embodiment of the present invention.

[0034] Figure 6 It is a curve diagram of the sound absorption coefficient of the sound-absorbing ceramic material of the comparative example.

[0035] Figure 7 This is a SEM electron microscope image of the sound-absorbing ceramic material of the comparative example.

[0036] Figure 8 Another SEM electron microscope image of the sound-absorbing ceramic material of the comparative example.

[0037] Fig. 9 The figure is a diagram of the surface condition of the ceramic green body after demoulding of the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION

[0038] The preparation method of the environmentally friendly microporous sound-absorbing ceramic of the present invention comprises the following steps: in the process of ceramic slurry injection molding, after the ceramic slurry is injected into the mold, a non-woven fabric is covered on the surface of the ceramic slurry in the mold, and the mold is left to stand; the non-woven fabric is then removed, and the green body is demolded to obtain the green body; the green body is dried and sintered, thereby obtaining the environmentally friendly microporous sound-absorbing ceramic.

[0039] In the gel injection molding process, the drying of the ceramic body is a very critical process, which has an important impact on the structure and performance of the final product. In the injection molding curing molding process, the present invention covers the surface of the ceramic slurry in the mold with a non-woven fabric, which can reduce the evaporation rate of water on the surface of the body, reduce the concentration gradient of water between the body and the environment as much as possible, control the dehydration rate of the body, and maintain the consistency of water diffusion inside and outside the body, thereby avoiding the occurrence of phenomena such as body cracking.

[0040] More specifically, the nonwoven fabric can be a water-permeable nonwoven fabric made of various materials such as polyester fiber nonwoven fabric and terylene nonwoven fabric, and polyester fiber nonwoven fabric is preferably used. The thickness of the nonwoven fabric can be 0.1 mm to 1 mm, and more preferably 0.3 mm.

[0041] In some embodiments, the ceramic body is a large-sized component. Accordingly, the mold can be optionally polygonal, including rectangular, square, regular geometric shape, etc., wherein at least one side is ≥ 20 cm. The mold can also be circular, and its circular diameter is ≥ 20 cm.

[0042] During the above-mentioned ceramic slurry injection molding and static molding process, cracking during the drying process after demoulding is avoided by covering with non-woven fabric, which greatly improves the yield rate of ceramic material products, improves the material production efficiency, and facilitates the large-scale production of porous ceramic sound-absorbing material products; for the injection molding of ceramic slurry with river and lake bottom mud or other construction waste as raw materials, this method is also beneficial to the batch treatment and disposal of solid waste.

[0043] For other steps in the preparation method after injection molding, some preferred schemes are as follows.

[0044] The static mold-forming time is 16 to 28 hours.

[0045] The drying temperature is 40-55° C., and the moisture content of the green body after drying is ≤3%. The drying device can use equipment such as an oven.

[0046] The sintering comprises: placing the dried green body in a sintering furnace, raising the sintering temperature to 1200-1350° C. at a rate of 5° C. / min, keeping the temperature for 2 hours, and then cooling the green body to room temperature with the furnace and taking out the green body to obtain the sound absorbing ceramic.

[0047] For the preparation of ceramic slurry, in some implementation schemes, the ceramic slurry is used to prepare environmentally friendly microporous sound-absorbing ceramic materials, and the slurry is mainly prepared using river and lake sediments. The preparation method of the ceramic slurry includes: mixing river and lake sediments, fly ash, diatomaceous earth, expansion agent, dispersant, and gelling agent, adding water to form an initial slurry with a solid content (i.e., solid phase volume fraction) of 38-50%; ball milling the initial slurry to obtain a premixed liquid; adding a foaming agent to the premixed liquid, stirring once, and then adding a foam stabilizer, stirring twice to obtain a ceramic slurry.

[0048] In the above preparation method, the basic materials include river and lake sediment, fly ash and diatomaceous earth. As for the reagents used, the expansion agent is introduced to promote the expansion process of the ceramic slurry; the dispersant effectively prevents the material from settling or agglomerating in the liquid; the gelling agent is used to promote the coagulation and stability of the ceramic slurry; the foaming agent can introduce a pore structure into the ceramic slurry; and the foam stabilizer is used to control the stability of the bubbles in the ceramic slurry.

[0049] For the above-mentioned primary stirring and secondary stirring, the primary stirring is low-speed stirring, and the secondary stirring is high-speed stirring, that is, the rotation speed of the primary stirring is higher than that of the secondary stirring. Preferably, the rotation speed of the primary stirring is 600-800 rpm / min, and the stirring time is 2-4 min. Preferably, the rotation speed of the secondary stirring is 800-1000 rpm / min, and the stirring time is 1-2 min.

[0050] The foaming process is divided into two stirring steps. First, add the foaming agent and stir at a low speed, and then add the foam stabilizer for a second high-speed stirring, instead of adding the foaming agent and foam stabilizer at the same time and stirring together in the traditional method. Through the above means, the materials can be gradually mixed by stirring at a low speed first, while avoiding the splashing of the slurry. As the slurry is fully foamed, the materials can be mixed more fully by stirring at a high speed, thereby improving the efficiency and uniformity of the material mixing and ensuring the foaming multiple. After adding the foam stabilizer, the gel curing process is accelerated, reducing the possibility of small pores breaking into large pores and the collapse of the structure, improving the microstructure of the blank to a certain extent, increasing the integrity of the pore wall, and improving the compressive strength of the product. The above-mentioned sequential addition and stirring in batches are also beneficial to improving the acoustic properties of the porous sound-absorbing material.

[0051] As for the specific formula of ceramic slurry, in some implementation schemes, environmentally friendly microporous sound-absorbing ceramics are prepared using river and lake sediments. In terms of dry weight, the base material of the ceramic slurry includes 55-80 parts of river and lake sediments, 20-40 parts of fly ash, and 3-8 parts of diatomaceous earth; the agents added to the base material include 2-5% of expansion agent, 1-2% of dispersant, 1-2% of gelling agent, 0.8-2% of foaming agent, and 1-3% of foam stabilizer, in terms of mass fraction of the base material.

[0052] The above-mentioned basic materials include river and lake sediment, fly ash and diatomaceous earth. Specifically, river and lake sediment is collected and processed through drying, crushing and other processes to obtain fine sediment powder; fly ash is processed through fine powder to obtain fine-grained fly ash; diatomaceous earth is used as a reinforcing material to provide strength and stability for composite materials.

[0053] For the specific types of the above-mentioned agents, some optional solutions are as follows:

[0054] 1) The expansion agent is sodium bicarbonate.

[0055] 2) The foaming agent is sodium lauryl amphoacetate.

[0056] 3) The foam stabilizer is gluconolactone.

[0057] 4) The dispersant is any one or more of PMAA-NH4, water glass or sodium citrate.

[0058] 5) The gelling agent is any one or more combinations of plant glue, epoxy resin or sodium alginate.

[0059] The above schemes 1)-5) can be selected one by one, or multiple combinations thereof can be selected to form multiple feasible implementation plans.

[0060] As for the dispersant, a more preferred solution is that the dispersant is a combination of PMAA-NH4, water glass and sodium citrate; more specifically, the mass combination ratio of the three can be 2:1:1.

[0061] For the gelling agent, a more preferred embodiment is that the gelling agent is a combination of plant gum, epoxy resin and sodium alginate; more specifically, the mass combination ratio of the three can be 2:2:1.

[0062] In some embodiments, the ceramic slurry raw materials include: in weight percentage, 55-80% river and lake mud, 20-40% fly ash, and 3-8% diatomaceous earth; in terms of the mass fraction of the basic materials, the expansion agent (i.e., sodium bicarbonate) is 2-5wt.%, the dispersant (i.e., a combination of PMAA-NH4, water glass, and sodium citrate) is 1-2wt.%, the gelling agent (i.e., a combination of plant gum, epoxy resin, and sodium alginate) is 1-2wt.%, the foaming agent is sodium laurylamphoacetate is 0.8-2wt.%, and the foam stabilizer is gluconolactone is 1-3wt.%.

[0063] Furthermore, in some embodiments, the ceramic slurry raw materials include: calculated by weight percentage, 70% river and lake sediment powder, 22% fly ash, and 8% diatomaceous earth; calculated by mass fraction of the basic materials, 3% of the expansion agent sodium bicarbonate, 1.5% of the foaming agent sodium laurylamphoacetate, 2% of the dispersant (PMAA-NH4, water glass, sodium citrate), 3% of the foam stabilizer gluconolactone, and 2% of the gelling agent (vegetable gum, epoxy resin, sodium alginate).

[0064] In the above scheme, the sound-absorbing material uses river and lake sediment and fly ash, a solid waste from coal combustion, as the main raw materials, with polymethyl methacrylate derivative PMAA-NH4, water glass, and sodium citrate as dispersants, plant gum, epoxy resin, and sodium alginate as gelling agents, sodium lauryl amphoteric acetate as foaming agents, sodium bicarbonate as an expansion agent, and gluconolactone as a foam stabilizer. The gel foaming injection molding method is used to prepare environmentally friendly microporous sound-absorbing ceramics, which can be used as a sound absorption method to solve noise pollution problems in tunnels, subways, highway sound absorption barriers, and indoor places.

[0065] like Figure 1 As shown, in some embodiments, the preparation method steps are:

[0066] (1) Collect river and lake sediments, dry them in the sun, and crush them to obtain uniform and fine sediment powder;

[0067] (2) According to the weight percentage, 50-80 parts of river and lake sediment, 20-40 parts of fly ash, 3-8 parts of diatomaceous earth, and the total amount of the three base materials is 100 parts; according to the mass fraction of the chemical agent to the dry weight of the base material, 2-5% of the expansion agent (sodium bicarbonate), 1-2% of the dispersant PMAA-NH4, water glass and sodium citrate (the ratio of the three is 2:1:1), and 1-2% of the gelling agent plant glue, epoxy resin and sodium alginate (the ratio of the three is 2:2:1) are mixed, and deionized water is added to form an initial slurry with a solid content of 38-50 vol%;

[0068] Stir the initial slurry into a horizontal ball mill and mill it at a speed of 200 to 500 rpm for 2 to 5 hours to obtain a uniformly dispersed ceramic premix;

[0069] (3) introducing the uniform premix obtained in step (2) into a stirring container, adding 0.8-2% of sodium lauryl amphoacetate as a foaming agent to the premix, stirring, setting the stirring speed to 600-800 rpm, stirring for 2-4 min using an electric stirrer, then adding 1-3% of gluconolactone as a foam stabilizer, stirring at 800-1000 rpm for 1-2 min, to obtain a uniform, stable and fully foamed ceramic slurry;

[0070] (4) Inject the ceramic slurry obtained in step (3) into an acrylic mold, and cover the surface of the ceramic slurry with a 0.3 mm thick polyester fiber non-woven fabric to minimize the concentration gradient of water between the green body and the environment, control the dehydration rate of the green body, and maintain the consistency of water diffusion inside and outside the green body, thereby avoiding the occurrence of green body cracking and the like. Let it stand at room temperature for 16 to 28 hours until the ceramic slurry is solidified and formed, and then demold it to form a green body.

[0071] (5) The green body obtained in step (4) is placed in a sintering furnace, and the sintering temperature is increased to 1200-1350° C. at a rate of 5° C. / min, and kept at this temperature for 2 hours, and then cooled to room temperature in the furnace, and taken out to obtain the environmentally friendly microporous sound-absorbing ceramic material.

[0072] The present invention uses environmentally friendly microporous sound-absorbing ceramics prepared from river and lake bottom mud, which have a large number of porous structures inside, as sound-absorbing materials to achieve sound absorption performance. Add an appropriate amount of binder to the bottom mud raw material, mix and fix it to form a material with a certain strength. In addition, increasing the sintering temperature is conducive to consolidation, achieving its strength target requirements, and having good sound absorption performance, thereby coordinating the two performance indicators of acoustic performance and mechanical performance that are contradictory to the preparation requirements of open-pored ceramic sound-absorbing panels.

[0073] In some embodiments, the present invention can obtain porous sound-absorbing and noise-reducing ceramics with a thickness of 20 to 30 mm, a pore size range of 50 μm to 400 μm, high temperature resistance of not less than 1200°C, and a flexural strength of 50 to 100 MPa. It has good performance and meets special use requirements such as fire prevention, sound absorption and noise reduction, and a certain strength.

[0074] In some embodiments, the environmentally friendly microporous sound-absorbing ceramic material of the present invention has a thickness of 20 to 30 mm, a maximum sound absorption coefficient of 0.93 to 1, an average sound absorption coefficient of 0.48 to 0.82, a noise reduction coefficient (NRC) of 0.6 or more, and a half sound absorption bandwidth of more than 3000 Hz;

[0075] In some embodiments, the environmentally friendly microporous sound-absorbing ceramic of the present invention has a fireproof performance of A1 grade and a fire resistance time of more than 3 hours.

[0076] Based on the above schemes, the present invention also provides a sound barrier, which includes the environmentally friendly microporous sound-absorbing ceramics described in the present invention. In other words, the environmentally friendly microporous sound-absorbing ceramics described in the present invention can be used as sound-absorbing materials for sound barriers, and together with other components such as frame structures required for sound barriers, form a sound barrier, which is set in outdoor spaces such as tunnels and roads or indoors, etc., to solve the noise pollution problems in tunnels, subways, roads and indoors.

[0077] Example 1

[0078] Raw material formula: 55 parts of river and lake sediment, 40 parts of fly ash, 5 parts of diatomaceous earth; 3% of expansion agent (sodium bicarbonate), 1% of dispersant (PMAA-NH4, water glass, sodium citrate), 1% of gelling agent (vegetable gum, epoxy resin, sodium alginate), 1.2% of foaming agent sodium laurylamphoacetate, and 2% of foam stabilizer gluconolactone.

[0079] The river and lake bottom mud used in this embodiment includes the following components by weight percentage: SiO2 68.2-78.0%, Al2O3 10.2-11.94%, Fe2O3 4.6-5.1%, CaO 1.2-1.6%, MgO 0.4-1.0%, K2O 2.0-2.5%, Ti2O 0.8-1.0%, Na2O 0.4-0.5%; the remaining components are trace metals and ash impurities.

[0080] Raw material preparation: After the river and lake sludge is collected, it goes through processes such as drying and crushing to obtain fine sludge powder; the fly ash is finely powdered to obtain fine-grained fly ash; diatomaceous earth is used as a reinforcing material to provide strength and stability to the composite material; sodium bicarbonate expansion agent is introduced to promote the expansion process of the ceramic slurry; polymethyl methacrylate derivative PMAA-NH4, water glass and sodium citrate are used as dispersants to effectively prevent them from precipitating or aggregating in the liquid; vegetable gum, epoxy resin and sodium alginate are used as gelling agents to promote the coagulation and stability of the ceramic slurry; sodium lauryl amphoteric acetate is used as a foaming agent to introduce a pore structure into the ceramic slurry; gluconolactone is used as a foam stabilizer to control the stability of the bubbles.

[0081] Preparation of ceramic premixed slurry: Mix river and lake sediment, fly ash, diatomaceous earth and other basic materials according to the predetermined weight fraction and mass fraction. Add the expansion agent sodium bicarbonate, dispersant PMAA-NH4, water glass and sodium citrate, gelling agent plant glue, epoxy resin and sodium alginate to the basic material mixture and mix. Add an appropriate amount of deionized water and stir appropriately to obtain a uniformly dispersed ceramic initial slurry with a solid content of 40%. Place the slurry in a ball mill and ball mill at a speed of 300rmp / min for 5 hours to obtain a uniformly dispersed premixed liquid.

[0082] Foaming and condensation: Transfer the uniform premix to a stirring container. Gradually add sodium laurylamphoacetate as a foaming agent and stir once, i.e., stir at a stirring speed of 600 rpm for 4 minutes to form a uniform foaming slurry. Add gluconolactone foam stabilizer and stir twice, i.e., stir at a stirring speed of 800 rpm for 2 minutes to stabilize the generation of bubbles.

[0083] Preparation of green body: Stably foamed ceramic slurry is introduced into an acrylic mold, and a 0.3mm polyester fiber non-woven fabric is covered on the surface of the slurry. The green body is left standing at room temperature for 18 hours to allow the ceramic slurry to gradually condense and form a green body, and then the surface non-woven fabric is removed and demolded. After demolding, the green body is dried in an oven at 50°C for 24 hours. The green body is taken out of the mold and is ready to enter the sintering stage.

[0084] Sintering and cooling: The green body is placed in a sintering furnace and gradually heated up at a rate of 5°C / min. The temperature is raised to 1160°C and kept for 2 hours, then begins to cool with the furnace to gradually solidify the ceramic material. After isothermal cooling, it is taken out of the furnace to obtain an environmentally friendly microporous sound-absorbing ceramic material with a microporous structure.

[0085] The environmentally friendly microporous sound-absorbing ceramic material prepared in this embodiment was subjected to material characterization and analysis. Figure 2 This is a CT characterization image of the sound-absorbing ceramic material, showing that the material has an open-pore structure. Figure 3 and Figure 4 This is a SEM characterization image of the sound-absorbing ceramic material, showing that there are a large number of interconnected pores inside, and the pore size distribution is about 40-300μm.

[0086] Example 2

[0087] Raw material formula: 60 parts of river and lake sediment, 35 parts of fly ash, 5 parts of diatomaceous earth, 4% of expansion agent (sodium bicarbonate), 1% of dispersant (PMAA-NH4, water glass, sodium citrate), 2% of gelling agent (vegetable glue, epoxy resin, sodium alginate), 1.0% of foaming agent sodium laurylamphoacetate, and 1% of foam stabilizer gluconolactone.

[0088] The preparation method is the same as that of Example 1, except that after sodium laurylamphoacetate is added as a foaming agent, stirring is performed once at a stirring speed of 700 rpm for 3 minutes to obtain a uniformly foamed slurry.

[0089] Example 3

[0090] Raw material formula: 80 parts of river and lake sediment, 17 parts of fly ash, 3 parts of diatomaceous earth; 3.5% expansion agent (sodium bicarbonate), 1.5% dispersant (PMAA-NH4, water glass, sodium citrate), 1.5% gelling agent (vegetable glue, epoxy resin, sodium alginate), 2.0% foaming agent sodium laurylamphoacetate, and 3% foam stabilizer gluconolactone.

[0091] The preparation method is the same as that of Example 1. The difference is that after adding sodium lauryl amphoacetate as a foaming agent, stirring is performed once at a stirring speed of 800 rpm for 4 minutes to obtain a uniformly foamed slurry.

[0092] Example 4

[0093] Raw material formula: 70 parts of river and lake sediment, 22 parts of fly ash, 8 parts of diatomaceous earth, 3% of expansion agent (sodium bicarbonate), 2% of dispersant (PMAA-NH4, water glass, sodium citrate), 1.5% of gelling agent (vegetable glue, epoxy resin, sodium alginate), 1.5% of foaming agent sodium laurylamphoacetate, and 3% of foam stabilizer gluconolactone.

[0094] The preparation method is the same as that of Example 1. The difference is that after adding sodium lauryl amphoacetate as a foaming agent, stirring is performed at a stirring speed of 800 rpm for 2 minutes to obtain a uniformly foamed slurry.

[0095] Example 5

[0096] Raw material formula: 55 parts of river and lake sediment, 37 parts of fly ash, 8 parts of diatomaceous earth, 2% of expansion agent (sodium bicarbonate), 1.5% of dispersant (PMAA-NH4, water glass, sodium citrate), 1.5% of gelling agent (vegetable glue, epoxy resin, sodium alginate), 0.8% of foaming agent sodium laurylamphoacetate, and 2% of foam stabilizer gluconolactone.

[0097] The preparation method is the same as that of Example 1. The difference is that after adding sodium lauryl amphoacetate as a foaming agent, stirring is performed at a stirring speed of 700 rpm for 3 minutes to obtain a uniformly foamed slurry.

[0098] Example 6

[0099] Raw material formula: 77 parts of river and lake sediment, 15 parts of fly ash, 8 parts of diatomaceous earth, 5% of expansion agent (sodium bicarbonate), 2% of dispersant (PMAA-NH4, water glass, sodium citrate), 1.0% of gelling agent (vegetable gum, epoxy resin, sodium alginate), 2.0% of foaming agent sodium laurylamphoacetate, and 2% of foam stabilizer gluconolactone.

[0100] The preparation method is the same as that of Example 1. The difference is that after adding sodium lauryl amphoacetate as a foaming agent, stirring is performed at a stirring speed of 600 rpm for 4 minutes to obtain a uniformly foamed slurry.

[0101] For the convenience of description, the raw material formulas and preparation method parameters in the above-mentioned Examples 1-6 are listed in a table, as shown in Table 1.

[0102] Table 1

[0103]

[0104]

[0105] Table 2 is a table of performance microscopic parameters of environmentally friendly microporous sound-absorbing ceramics obtained in various embodiments of the preparation method of the present invention.

[0106] Table 2

[0107]

[0108] The parameter data in Table 2 show that the environmentally friendly microporous sound-absorbing ceramics obtained in each embodiment have a noise reduction coefficient of 0.52-0.62. Figure 5 1 is a curve diagram of the sound absorption coefficient of the environmentally friendly microporous sound-absorbing ceramics obtained in Examples 1-4 at different frequencies. Figure 5 It can be seen that the sound absorption coefficient of the sound-absorbing ceramics of each embodiment at 1khz-2khz is greater than 0.75, and the highest value of the sound absorption coefficient is 0.99, indicating that the sound-absorbing ceramic material of the present invention has a good sound absorption effect on traffic noise with a spectrum concentrated in 1khz-2khz.

[0109] The raw material formula and main preparation method of Comparative Examples 1-4 are the same as those of Example 4, except that the specific operation method in the foaming-foam stabilization step is different.

[0110] Comparative Example 1 and Comparative Example 2: The foaming agent and the foam stabilizer were added simultaneously and stirred for foaming before being injected into the mold.

[0111] Comparative Examples 3 and 4: The foaming agent is added first, stirred once, and then the foam stabilizer is added and stirred twice. The time setting for the first time is extended, exceeding the time for the first time stirring of the embodiment of the present invention.

[0112] For the convenience of description, the specific operation methods of Comparative Examples 1-4 are listed in a table, as shown in Table 3 below.

[0113] Table 3

[0114]

[0115] Table 4 below is a table of microscopic parameters of the environmentally friendly microporous sound-absorbing ceramics obtained in Comparative Examples 1-4.

[0116] Table 4

[0117] Parameter Item Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Porosity 48% 52% 53% 56% <![CDATA[Flow resistance rate (unit: Pa·s·m -3 )]]> 48943 45037 47386 42852 0~6300Hz sound absorption coefficient (range) 0.08~0.62 0.09~0.57 0.07~0.60 0.08~0.54 Noise Reduction Coefficient 0.41 0.35 0.37 0.38 Compressive strength (unit: MPa) 3.6 3.6 3.3 4.2

[0118] It can be seen from the data in Table 4 that the mechanical properties of Comparative Examples 1-4, namely the compressive strength, are relatively high, but the key acoustic performance parameters are relatively poor, and the materials are difficult to be used in sound absorption. Figure 6 The sound absorption coefficient curves of the environmentally friendly microporous sound-absorbing ceramics prepared in Comparative Examples 1-4 at different sound wave frequencies are shown in FIG. Figure 6 It can be seen that the sound absorption coefficient of the sound absorbing material in the frequency range of 500-6000 Hz is 0.3-0.7. Compared with Example 4, its acoustic performance is reduced. Figure 7 and Figure 8The SEM characterization images of the open-pore ceramic sound-absorbing panels of Comparative Examples 1 and 2 show that the internal pores are greatly reduced and are basically closed pores, with a pore size distribution of about 20-100 μm.

[0119] For comparative examples 1-4, after the foaming agent and the foam stabilizer are added together in comparative example 1-2, the foaming rate of the slurry decreases because the foam stabilizer reduces the foaming ability of the surfactant foaming agent to a certain extent; for comparative examples 3-4, the stirring time is too long after the foaming agent is added, which may lead to defoaming, and the small pores are broken to form large pores, which reduces the connected pores, so the open porosity of the ceramic sound-absorbing board decreases. From the material characterization image, that is, Figure 7 and Figure 8 It can also be seen from the above that the porosity of the material is reduced and the pores are closed, and the sound cannot dissipate in the connected pores, thereby reducing the sound absorption coefficient. As described above, from the effects of Comparative Examples 1-4, it can be seen that the technical means related to the foaming and foam stabilization links in the preparation method of the present invention can bring good results.

[0120] Comparative Examples 5-7 conducted comparative tests on the drying step after standing and the specific drying method and other related technical means. The raw material formula and main preparation method of Comparative Examples 5-7 are the same as those of Example 4, except for the method used after drying.

[0121] Comparative Example 5

[0122] After the slurry was cast, it was left to dry at room temperature for 18 hours and then dried.

[0123] Comparative Example 6

[0124] After the slurry was injected into the mold, the mold was sealed and frozen at -50 to -30°C for 10 hours. After demolding, the mold was dried in an oven at 50°C for 10 hours.

[0125] Comparative Example 7

[0126] During the preparation process, a toughening agent polyvinyl alcohol fiber was added, with a fiber diameter of 15 μm and an addition amount of 2%. The fibers were added together with a foaming agent and stirred. The slurry was allowed to stand for 40 hours and dried at room temperature.

[0127] Comparative Example 5 was dried at room temperature after injection molding, and cracks appeared after 15 hours, and the sample could not be processed subsequently. Comparative Example 6 was taken out after freezing, and dried in a 50°C oven for 2 hours, and cracks appeared. The cracks were radial, and the sample could not be processed subsequently. Comparative Example 7 was left to stand for 40 hours after drying, and cracks appeared after the sample was fired.

[0128] More specifically, the surface conditions of the green bodies after demoulding of Examples 1-4 and the green bodies of Comparative Examples 5-7 are as follows: Fig. 9 shown. Fig. 9It can be seen that comparative example 5 cracked after drying at room temperature, comparative example 6 cracked after drying in an oven, and comparative example 7 cracked after firing. The surface of the sample green bodies prepared in embodiments 1-4 was intact and good without cracks, and the samples could be subjected to subsequent processing such as sintering.

[0129] In the gel injection molding process, the drying of the ceramic blank is a very critical process, which has an important impact on the structure and performance of the product. During the drying process, it is necessary to control the ambient temperature and humidity, try to reduce the concentration gradient of water between the blank and the environment, control the dehydration rate of the blank, and maintain the consistency of water diffusion inside and outside the blank, so as to avoid the occurrence of phenomena such as cracking of the blank. Usually, large-sized (greater than 20cm) ceramic wet blanks are more likely to deform and crack during the drying process, and the currently commonly used freeze-drying method and toughening agent addition method are suitable for gel injection molding, and this method requires the solid content of the slurry to be greater than 50%, which is not effective for the case where the solid content is less than 50%. Therefore, it is necessary to provide a new low-cost manufacturing method for the preparation of large-sized ceramic parts. The preparation method of the present invention adopts the surface covering polyester fiber non-woven fabric to reduce the surface water evaporation rate, ensure the consistency of internal and external water diffusion, avoid the generation of cracks, have good effects and can be promoted.

[0130] The present invention has been described in detail above in conjunction with specific implementation methods and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art will appreciate that, without departing from the spirit and scope of the present invention, various equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention.

Claims

1. A method for preparing an environmentally friendly microporous sound-absorbing ceramic, comprising injection molding a ceramic slurry, characterized in that: Injecting ceramic slurry into a mold, covering the surface of the ceramic slurry in the mold with non-woven fabric, and allowing it to stand to form a mold; Then, the non-woven fabric is removed and the green body is demoulded to obtain the green body; the green body is dried and sintered; The preparation method of the ceramic slurry comprises: mixing river and lake bottom mud, fly ash, diatomaceous earth, an expander, a dispersant, and a gelling agent, adding water to form an initial slurry, wherein the solid content of the initial slurry is 38-50 vol%; ball milling the initial slurry to obtain a premixed liquid; adding a foaming agent to the premixed liquid, stirring once, and then adding a foam stabilizer, stirring twice, to obtain a ceramic slurry; The components of the ceramic slurry, calculated by dry weight, include 55-80 parts of river and lake sediment, 20-40 parts of fly ash, and 3-8 parts of diatomaceous earth as the basic material; the agents added to the basic material include 2-5% of expansion agent, 1-2% of dispersant, 1-2% of gelling agent, 0.8-2% of foaming agent, and 1-3% of foam stabilizer in terms of mass fraction of the basic material.

2. The preparation method according to claim 1, characterized in that: The non-woven fabric is a polyester fiber water-permeable non-woven fabric; the thickness of the non-woven fabric is 0.3 mm.

3. The preparation method according to claim 1, characterized in that: The mold is circular or polygonal; the diameter of the circle is ≥20cm, and the length of at least one side of the polygon is ≥20cm.

4. The preparation method according to claim 1, characterized in that: The rotation speed of the primary stirring is 600-800 rpm, and the stirring time is 2-4 minutes.

5. The preparation method according to claim 1, characterized in that: The speed of the initial slurry ball milling is 200-500 rpm, and the ball milling time is 2-5 hours; the speed of the secondary stirring is 800-1000 rpm, and the stirring time is 1-2 minutes.

6. Environmentally friendly microporous sound-absorbing ceramics prepared by the preparation method according to any one of claims 1 to 5.

7. The environmentally friendly microporous sound-absorbing ceramic according to claim 6, characterized in that: The dispersant is any one or more combinations of PMAA-NH4, water glass or sodium citrate; the gelling agent is any one or more combinations of plant glue, epoxy resin or sodium alginate.

8. A sound barrier, characterized in that: The environmentally friendly microporous sound-absorbing ceramic comprises the environmentally friendly microporous sound-absorbing ceramic prepared by the preparation method described in any one of claims 1 to 5 or the environmentally friendly microporous sound-absorbing ceramic described in claim 7.

Citation Information

Patent Citations

  • Drying method for long bar shaped ceramic base substrate

    CN101293774A

  • High-temperature-resistant foam ceramic prepared from FCC (fluid catalytic cracking) waste catalyst and preparation method of high-temperature-resistant foam ceramic

    CN110002855A

  • Ecological perforated ceramic sound absorption material prepared from sludge and preparation method of ecological perforated ceramic sound absorption material

    CN116283227A